Orbital-scale vegetation-ocean-atmosphere linkages in western Japan during the last 550 ka based on a pollen record from the IODP site U1427 in the Japan Sea. (1st September 2021) - Hayashi, Ryoma; Sagawa, Takuya; Irino, Tomohisa; Tada, Ryuji
Abstract: Climate and vegetation in Japan are strongly influenced by the East Asian Monsoon (EAM) and the ocean environment of the Japan Sea. This study discusses the findings from a new pollen record from Integrated Ocean Drilling Program Site U1427, situated off the northern coast of the Honshu Island in western Japan, which allows for direct comparisons with other oceanographic proxies from this area. Our findings demonstrate the orbital-scale vegetation changes in this area and their land-ocean-atmosphere linkages during the last 550 ka. During surface-water freshening events in the Japan Sea, likely associated with colder water temperatures caused by the very low eustatic sea levels and the consequent isolation from the surrounding seas during the full-glacial periods, cold-cool conifer forests became dominant under the extremely dry pseudo-continental conditions in the Japanese islands. In contrast, temperate broadleaf forests increased rapidly when the surface-freshening events ended and a weak inflow of warm water began at the onset of deglaciation, in addition to the rapid atmospheric climate warming during termination periods. During the intermediate periods between the full interglacial to the full-glacial, the Tp ratio (pollen temperature index) increased in association with the summer insolation maxima caused by the Earth's precession cycle that coincide with Chinese stalagmite negative δ 18 O peaks, whereas Cryptomeria pollen abundance (high-precipitation index) increased in association with the winter insolation maxima. Those orbital-scale vegetation fluctuations were attributed to the changes in seasonal temperature and precipitation patterns, where were influenced by the EAM changes that were associated with seasonal insolation changes around the Japanese archipelago. Cryptomeria forests likely developed under cool and wet conditions throughout a year with low seasonal contrasts, whereas deciduous broadleaf forests increased under condition of high seasonality with cool summers and colder, drier winters. Alternating fluctuations between the Tp ratio and Cryptomeria pollen abundance following the insolation changes were typically observed after MIS 9 and are thought to have been affected by the periodicity shift in the EAM fluctuations across the Mid-Brunhes Event. Highlights: A new pollen record from the Japan Sea demonstrated vegetation-ocean-atmosphere linkages during the last 550 ka. Surface-water freshening events in the Japan Sea enhanced the development of cold-cool conifer forests in the full glacial. Weak inflows of the Tsushima Warm Current at the onset of deglaciation enhanced the increase of temperate broadleaf forests. Cryptomeria abundance increased during the winter insolation maxima under cool and wet conditions during all seasons. Fluctuations in Cryptomeria abundance suggested a periodicity shift in the East Asian Monsoon across the Mid-Brunhes Event.